A 50-Year Commitment to American Indian and Alaska Native Women. Issue 4 (October 2020) - Waxman, Alan G.; Haffner, William H.J.; Howe, Jean; Wilder, Kathleen; Ogburn, Tony; Murphy, Neil; Espey, Eve; Tucker, J. Martin; Bruegl, Amanda; Locke, Elaine; Malloy, Yvonne
Abstract : Since 1970, the American College of Obstetricians and Gynecologists' Committee on American Indian and Alaska Native Women's Health has partnered with the Indian Health Service and health care facilities serving Native American women to improve quality of care in both rural and urban settings. Needs assessments have included formal surveys, expert panels, consensus conferences, and onsite program reviews. Improved care has been achieved through continuing professional education, recruitment of volunteer obstetrician–gynecologists, advocacy, and close collaboration at the local and national levels. The inclusive and multifaceted approach of this program should provide an effective model for collaborations between specialty societies and health care professionals providing primary care services that can reduce health disparities in underserved populations. Abstract : The American College of Obstetricians and Gynecologists' collaboration with health care organizations serving Native American women provides a model for reducing racial disparities while improving women's health care.